A comparative study of biomechanical variables between the stages of performing the skills (Blanik) and (Lu Yu Fu)On the jumping platform for the player qualifying for the final of the World Cup series in Qatar - Amin, Mumtaz; Alalawi, Ismaeel; Hussein, Yasir (Journal of Physical Education, 2024)
The idea of ​​the research came from the performance of one of the players who qualified for the final of the World Cup series in gymnastics held in Doha, the capital of Qatar, for the year 2023-2024 on the vaulting platform. In the individual final of the apparatus, this player performed two skills, the first was the “Blank” skill and the second was the “LuYuFu” skill. The two skills are different only in terms of direction. The first skill is performed while facing the device, that is, in the front direction, while the second skill is performed by the player from the back direction. Here, the research was done to find out what differences will appear in the biomechanical variables between both skills, and on the basis of dividing the movement stages, which is the vault table strike, then the first flight, then the push on the platform, then the second flight, and finally the landing. The performance of the player was photographed from the side with a camera with a speed of 240 images/second, perpendicular to the path line of the motor performance of both skills. And during his role, as being in the fifth place in the championship of the individual apparatus, after which motor analysis procedures were carried out using the MaxTRAQ program and the biomechanical variables common to the two skills were adopted according to the technical division for the performance stages on vault table. A comparison was made between the values ​​of the variables according to each stage between the two skills, through which we noticed a difference in the body position at the vault strike through the distance and speed of landing on the vault table, which was reflected in the force of the strike. The results were in favor of the first skill, as is the case with the first flight, and the reason for this is due to the fact that The player will resort to change his direction in the second skill in order to do the Arabian jumb, i.e. half turn, to land on the platform to prepare for the second push and flight. As for the second stage of flight and landing, it was in favor of the second skill because when landing, the body is facing the horse, while in the first skill, the player’s back is facing the horse. The process of adjusting the back landing is better than adjusting the front landing, with the exception of the deviation that occurred at the end of the skill due to the body twist over the vault table. Keywords: biomechanical variables, performance stages, (Lu Yu Fu), (Blank), vault table, qualified player for the final, World Cup series in Qatar.